FI-SURF algorithm for image copy-flip-move forgery detection - IYan L; IUNian L; HANGBin Z; UANKai-guo Y; ANGYi-xian Y (Tongxin xuebao)
FI-SURF (flip invariant SURF) algorithm was proposed,for the consideration of the copy-move forgery detec-tion of digital images.The arrangement of the SURF (speeded-up robust features) descriptor after image flip was studied.After extract the SURF interest points,rearrange the descriptors,the interest points can still be matched even under the condition of copy-flip-move.The experiment results show that FI-SURF not only reserved the advantage of SURF,but also can detect the copy-flip-move forgery,and can locate the duplicated region.